Learning by Projects: A Pedagogical Experience for the Construction of Learning Spaces Inside and Outside of the Classroom - Arias Sandoval, Leonel (2017)
This essay has the aim to describe the pedagogical experiences of learning by projects from the educational practice in an urban school of Alajuela city, starting from the inclusion of educational projects in the classroom. This is due to a series of pedagogical strategies that involve the development of some activities, technical and consistent didactic resources with the conceptual curricular contents, such as conceptual, procedural and attitudinal ones. The pedagogical projects are placed within the constructivist philosophical framework that involves a methodological strategy that integrates the necessary procedures to develop individual and collective learning based on innovative activities. As a conclusion, each project responds to a specific context; therefore, the strategies that are going to be developed in each of the institutions cannot be generalized; besides, the accompaniment of the teacher in the classroom is fundamental during work organization.